Inclusión educativa - Aguagallo Córdova, Lliliana Marivel (2017)
The study of the Educational Inclusion, it had as aim of investigation to identify children and girls with special education associated needs or not to the disability inside the teaching learning process. The research problem has been determined considering the deficient strategies of educational inclusion in Once de Noviembre Educative Unit, due to teachers must know the teaching learning process versus Inclusive Education. The methodological design of this research project is framed in the synthetic analytical method, which was useful to identify the problems that students have with special educational needs associated or not to the disability as object of. With the purpose of obtaining information to this investigation survey and questionnaire were done, also analysis and discussion of information, by means of which it was possible to determine that the students present problems of dyslexia, dyscalculia and hyperactivity. This project for being of educational character had a social impact and in turn formative, since it involves the education actors, who take charge of the integral formation of the children and girls with and without Educational Special Needs, to promote the autonomy and the responsibility in the children and girls in the educational process.